Analisis Faktor-Faktor yang Mempengaruhi Rendahnya Minat Belajar Matematika Siswa di SMPN 5 Satap Kuala Mandor B - Bahri, Irfan; Susiaty, Utin Desy; Hartono, Hartono (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the factors that influence the low interest in studying mathematics among eighth-grade students at SMPN 5 Satap Kuala Mandor B. The study employs a descriptive qualitative approach, identifying internal and external factors that affect students' motivation and interest in mathematics. Data were collected through questionnaires, interviews, and observations. The data analysis technique used is qualitative data analysis, which involves the stages of data reduction, data presentation, and conclusion drawing. The research results show that negative perceptions of mathematics, low internal motivation, and the influence of social and school environments are the main factors that lead to low student interest in learning mathematics. These findings are expected to provide guidance for the development of more effective learning strategies in the future. Keywords: Learning interest, mathematics, psychological factors, external factors, SMPN 5 Satap Kuala Mandor B.